Effects of 12-week overground walking training at ventilatory threshold velocity in type 2 diabetic women - Belli, Taisa [UNESP]; Ribeiro, Luiz Fernando Paulino [UNESP]; Ackermann, Marco Aurélio; Baldissera, Vilmar; Gobatto, Claudio Alexandre; Galdino da Silva, Rozinaldo (Elsevier, 2011)
This study analyzed the effects of overground walking training at ventilatory threshold (VT) velocity on glycaemic control, body composition, physical fitness and lipid profile in DM2 women. Nineteen sedentary patients were randomly assigned to a control group (CG; n=10, 55.9±2.2 years) or a trained group (TG; n=9, 53.4±2.3 years). Both groups were subjected to anthropometric measures, a 12-h fasting blood sampling and a graded treadmill exercise test at baseline and after a 12-week period, during which TG followed a training program involving overground walking at VT velocity for 20-60min/session three times/week. Significant group×time interactions (P<0.05) in glycated hemoglobin (HbA1c), body mass, body mass index (BMI), peak oxygen uptake (VO 2peak) and exercise duration were observed as effects of training exercise, whereas intervention did not induced significant changes (P>0.05) in fasting blood glucose, submaximal fitness parameters and lipid profile. Our results suggest that overground walking training at VT velocity improves long term glycaemic control, body composition and exercise capacity, attesting for the relevance of this parameter as an effective strategy for the exercise intensity prescription in DM2 population. © 2011 Elsevier B.V.
Keywords: Exercise; Fitness; HbA1c; Type 2 diabetes; Ventilatory threshold; glycosylated hemoglobin; metformin; sulfonylurea; adult; anthropometry; body composition; body mass; clinical article; controlled study; diet restriction; exercise; female; fitness; glycemic control; human; lipid analysis; lung capacity; non insulin dependent diabetes mellitus; outcome assessment; oxygen consumption; prescription; sitting; training; treadmill exercise; treatment duration; walking; Anthropometry; Blood Glucose; Body Composition; Body Mass Index; Diabetes Mellitus, Type 2; Energy Intake; Exercise Therapy; Fasting; Female; Hemoglobin A, Glycosylated; Humans; Middle Aged